Pengembangan E-Modul Materi Sistem Imun Sebagai Bahan Ajar Biologi Siswa Kelas XI IPA Di SMAN 1 Pringgasela: (Development of E-Module of Immune System as Teaching Material for Biology of Grade XI Science Students at SMAN 1 Pringgasela, East Lombok) - Meri Nurianti; Maya Ekaningtias; Nurmiati (Otus Education: Jurnal Biologi dan Pendidikan Biologi, 2024)
This research aims to develop an e-module of immune system material as biology teaching material for grade XI science students at SMAN 1 Pringgasela. This type of research is development research. The development model used is 4D Thiagarajan et al., (1947) which consists of stages of define, design, development, and disseminate. Data was obtained through e-module validation by validators consisting of material experts, media experts, as well as biology teachers and students using validation sheets (questionnaires). The questionnaire data analysis technique uses calculations and feasibility criteria adopted from Sugiyono (2015). The results of expert validation and the responses of teachers and students showed that the biology e-module developed was feasible to use with an average percentage of 92.5% (material experts), 80% (media experts), 80% (biology teachers), and 91.47% (students). Based on the results of the study, it shows that the e-module product of immune system material is declared suitable to be used as a source of biology teaching materials in supporting the learning process of grade XI science students at SMAN 1 Pringgasela.